Procesos de orientación para la inserción sociolaboral de personas con especiales dificultades de acceso al mercado de trabajo. Un modelo de orientación para la inserción - Jurado de los Santos, Pedro; Olmos Rueda, Patricia (REOP - Revista Española de Orientación y Psicopedagogía, 2014)
RESUMEN En este trabajo, abordaremos algunos de los aspectos relacionados con los procesos de orientación para la inserción sociolaboral del colectivo de personas con especiales dificultades de acceso al mercado de trabajo, concretamente del colectivo de personas que han sido diagnosticadas con inteligencia límite. Analizaremos las principales dificultades que nuestra población destinataria encuentra a la hora de acceder al mercado de trabajo, los objetivos que persiguen los procesos de orientación, el papel de las competencias en estos procesos; especialmente las competencias de empleabilidad y adaptabilidad; y el planteamiento aproximativo a un modelo de orientación para la inserción laboral a partir de la autopercepción de las competencias. ABSTRACT In this paper, we are going to talk about some aspects related to the guidance processes for social and labour integration of persons with special difficulties to the work market access, focusing on the collective of persons who have been diagnosed with limit intelligence. We are going to analyze the major challenges that our study collective find to the work market access, the aims of the guidance processes, and the role of competences in this process, especially de rol of employability and adaptability competences. For that, we propose a guidance model for the employability of this collective, which contrasted with the skills required in terms of work contexts, will be enable the analysis and detection of needs that will guide the process of take decisions. The self-perception competences will be a key element in this guidance model if we will obtain an active and responsability involvement and participation of persons with limit intelligence in their process of training and guidance for incorporation into the work market. When our collective are aware of their competences, they will make it possible to self-identify themselves as capable and competent individuals, and instead, they are aware of their needs. It is the starting point of the guidance processes for social and labour integration of persons with special difficulties to the work market access.